1979
DOI: 10.1351/pac197951071473
|View full text |Cite
|
Sign up to set email alerts
|

Theory of gel permeation chromatography. Mechanism of separation and the influence of polymer-sorbent interaction

Abstract: -The displacement of hydrodynamic volume universal calibration curves to high retention volumes for some polymer-solvent systems in gel permeation chromatography is explained in terms of a network-limited separation consisting of a steric exclusion mechanism and a second mechanism resulting from polymer-sorbent interaction. This treatment is consistent with a thermodynamic interpretation of gel permeation chromatography in which the distribution coefficient (~ 1.0) for polymer-sorbent interaction is determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…(1)]. [20] The plot of t against V is given in Figure 4: The good-fit parameter (c 2 0.012) demonstrates the consistency of the V values within the series. Supramolecular properties: The above discussion of the 1 H NMR spectra already revealed that the dendrimers 1 n exhibit a tendency to aggregate which increases with increasing n. [11] Apolar solvents, such as cyclohexane or toluene, are particularly suitable for the formation of such aggregates; chloroform is less suitable because it strongly interacts with the electron-rich peripheral benzene rings.…”
Section: Resultsmentioning
confidence: 83%
“…(1)]. [20] The plot of t against V is given in Figure 4: The good-fit parameter (c 2 0.012) demonstrates the consistency of the V values within the series. Supramolecular properties: The above discussion of the 1 H NMR spectra already revealed that the dendrimers 1 n exhibit a tendency to aggregate which increases with increasing n. [11] Apolar solvents, such as cyclohexane or toluene, are particularly suitable for the formation of such aggregates; chloroform is less suitable because it strongly interacts with the electron-rich peripheral benzene rings.…”
Section: Resultsmentioning
confidence: 83%
“…The attractive enthalpic interactions in the latter SEC systems are as a rule unexpected. Typical example is the extensive retention of polystyrenes from dimethylformamide mobile phase on polystyrene/divinylbenzene column packings, which was for the first time observed by Dawkins 44. The practical aspects of enthalpic retention mechanisms in SEC will be discussed in Sections 3.4, 4.5, and 5.…”
Section: Macromolecular Substances Polymersmentioning
confidence: 93%
“…Because of the complexity and the size of the higher dendrimers, a full geometrical optimization was not possible; thus, we had to make some simplifying assumptions: 1) all bond lengths and bond angles correspond to standard values; 2) we assumed C 3 symmetry for the central tristyrylbenzene moiety and C 2 symmetry for the remainder dendrons; 3) interaction of the hexyloxy chains was neglected, the chains were directed in an all-trans conformation radially away from the peripheral benzene rings; 4) the torsions around the single bonds were driven until acceptable distances (340 ± 450 pm) between the aromatic units were reached. [20] The plot of t against V is given in Figure 4: The good-fit parameter (c 2 0.012) demonstrates the consistency of the V values within the series. Thus the disklike shape is transformed into Scheme 3.…”
Section: Resultsmentioning
confidence: 75%